Waiting for Treatment for Chronic Pain – a Survey of Existing Benchmarks: Toward Establishing Evidence-Based Benchmarks for Medically Acceptable Waiting Times - Mary E Lynch; Fiona A Campbell; Alexander J Clark; Michael J Dunbar; David Goldstein; Philip Peng; Jennifer Stinson; Helen Tupper; the Canadian Pain Society Wait Times Task Force (Pain Research and Management)
As medical costs escalate, health care resources must be prioritized. In this context, there is an increasing need for benchmarks and best practices in wait time management. In December 2005, the Canadian Pain Society struck a Task Force to identify benchmarks for acceptable wait times for treatment of chronic pain. The task force mandate included a systematic review and survey to identify national or international wait time benchmarks for chronic pain, proposed or in use, along with a review of the evidence upon which they are based. An extensive systematic review of the literature and a survey of International Association for the Study of Pain Chapter Presidents and key informants has identified that there are no established benchmarks or guidelines for acceptable wait times for the treatment of chronic pain in use in the world. In countries with generic guidelines or wait time standards that apply to all outpatient clinics, there have been significant challenges faced by pain clinics in meeting the established targets. Important next steps are to ensure appropriate additional research and the establishment of international benchmarks or guidelines for acceptable wait times for the treatment of chronic pain. This will facilitate advocacy for improved access to appropriate care for people suffering from chronic pain around the world.